Impact of Micro Finance Institutes (MFI’s) on the Growth of Small and Medium Enterprises (SMEs) in Khyber Pakhtunkhwa - SYED UZAIR; DR. FAHAD KHAN AFRIDI; DR. MUHAMMAD ADIL (Journal of Business & Tourism, 2021)
Economic stability is very necessary for the development of economy a country. For this purpose industrialization plays a positive role in fulfilling this achievement. The trend of borrowing from Micro Finance Institutions increases day by day as business activities takes place. Also from political stability Foreign Direct Investment takes place resulting in boosting and competitive environment for domestic investors. MFIs serving in all cities of Pakistan focus on enhancing business activities on domestic level. Each and every bank has its own microfinance institution departments focusing mainly on fulfilling the access to finance through some easy steps for starting new ventures. From past some years Pakistan is facing a lot different situations in country like Political Instability, Terrorism and Unemployment. Now in this situation there is lack of foreign investment in our country. Meanwhile, Domestic Level Small & Medium Enterprises faces a lot of challenges while financing their own SMEs. State bank of Pakistan introduces Business Support Fund through which every bank has to facilitate investors with loans to increase new ventures startup which in turns can help out the economy. Trend of MFIs and SMEs had increase in Khyber Pakhtunkhwa as well like Faisalabad, Karachi and Lahore so do demand for credit investment increases resulting in MFIs with new ideas and proposals.